2014
DOI: 10.1603/ec13167
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Transmission of ‘<I>Candidatus</I> Phytoplasma ulmi' by <I>Amplicephalus curtulus</I> (Hemiptera: Cicadellidae) and Its Effect on Ryegrass (<I>Lolium multiflorum</I> Cv. Tama)

Abstract: In Chile, phytoplasmas have been reported in sugar beet, grapevine, peony, and Chilean shrubs. 'Candidatus Phytoplasma ulmi' have been detected in plants of Ugni molinae Turczanínow (Myrtaceae) and the leafhopper Amplicephalus curtulus Linnavuori & DeLong. We evaluated the possibility of phytoplasma transmission from native plants to grasses by A. curtulus and the possible effect on the plant hosts. Newly emerged adults were placed in cages with phytoplasma-infected U. molinae for 72 h (acquisition access peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
4
16
0
Order By: Relevance
“…In this period, it was between 330 and 420 CPu GU ng À1 of insect DNA. In similar conditions, we previously demonstrated that A. curtulus suitably transmitted phytoplasma from 35 to 41 days after AAP (Arismendi et al, 2014), which supports the results presented here. Similar or lower values have been previously detected by quantitative PCR (Marzach ı & Bosco, 2005;Galetto et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this period, it was between 330 and 420 CPu GU ng À1 of insect DNA. In similar conditions, we previously demonstrated that A. curtulus suitably transmitted phytoplasma from 35 to 41 days after AAP (Arismendi et al, 2014), which supports the results presented here. Similar or lower values have been previously detected by quantitative PCR (Marzach ı & Bosco, 2005;Galetto et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Considering that the lowest value on the calibration curve was 8 fg in 1 ng of insect DNA (610 CPu GU ng À1 of insect DNA), real-time PCR values obtained in this period represent almost half of the minimum value used in the calibration curve. We showed that females have a high phytoplasma titer in their head-thorax section, higher than the minimum considered to allow transmission (Galetto et al, 2009), indicating that the period 35-45 days post-AAP could be considered a suitable transmission period (Arismendi et al, 2014). In this period, the phytoplasma may still be circulative, but not totally propagative.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Such differential distribution of phytoplasmas is probably due to the diversity and preferential distribution of their insect vectors. While some leafhopper vectors of phytoplasma, such as species of Dalbulus, have been detected in all Latin American countries (Nault, 1980(Nault, , 1983, others, such as Amplicephalus curtulus, have been detected only in Chile and Colombia (Alvarez et al, 2009;Arismendi et al, 2014).…”
Section: Phytoplasmas In Latin Americamentioning
confidence: 99%